The Hagiographical Tradition: Bede’s and Foxe’s Accounts of the Martyrdom of St. Alban - Cipriano, Rita (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2022)
By comparing the accounts of the martyrdom of the English proto-saint Alban written by Bede (c. 673-735) and John Foxe (1516/7-1587), this essay aims to analyse how the sixteenth-century author reworked the medieval genre of the passio to create a new history of the English Church that incorporated the martyrs of the Reformation movement.